(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Remote data unity checking (RDUC) permits checking the data integrity for the data put away on cloud. There are number of RDUC conventions have been proposed in the writing, however they experience the ill effects of issue of a mind-boggling key administration. In this venture, we propose another development of identity-based (IDbased) RDUC convention by making utilization of security key natives to diminish the framework many-sided quality and the expense for building up and dealing with the general population enter confirmation structure in PKI based RDUC plans. In our venture there are three principle ideas that are cloud server, user and third-party auditor (TPA). TPA gives the evidence that our data integrity is keep up or not, likewise we are additionally giving the security components. on the off chance that if the data is gets adjusted by the cloud server or unapproved individual then user gets their unique data from the fake server. Third Party Auditor (TPA) is in charge of checking the integrity of the cloud data in the interest of the cloud users in the event that if cloud user does not have room schedule-wise to screen their assets and integrity of data and returns the examining report to the cloud user.